The Reciprocal Causation of the ASK1-JNK1/2 Pathway and Endoplasmic Reticulum Stress in Diabetes-Induced Cognitive Decline - Wu, Yanqing; Yuan, Yuan; Wu, Chengbiao; Jiang, Ting; Wang, Beini; Xiong, Jun; Zheng, Peipei; Li, Yiyang; Xu, Jingyu; Xu, Ke; Liu, Yaqian; Li, Xiaokun; et al. (Frontiers in Cell and Developmental Biology, 2020)
Diabetes significantly induces cognitive dysfunction. Neuronal apoptosis is the main caused event for diabetes-induced cognitive decline (DICD). Apoptosis signal-regulating kinase 1 (ASK1) and endoplasmic reticulum (ER) stress are remarkably activated by diabetes. The role and relationship of ASK1-JNK1/2 signaling and ER stress in DICD has not yet been elucidated. In this study, we used db/db mice as DICD animal model, and confirmed that db/db mice displayed cognitive decline with inferior learning and memory function. Diabetes significantly induced morphological and structural changes, excessive neuronal apoptosis, Aβ1-42 largely deposition and synaptic dysfunction in the hippocampus. Mechanistic studies found that diabetes significantly triggered ASK1-JNK1/2 signaling activation and increased ER stress in the hippocampus. Moreover, diabetes enhanced the formation of the IRE1α-TRAF2-ASK1 complex, which promotes the crosstalk of ER stress and the ASK1-JNK1/2 pathway during DICD. Furthermore, 4-PBA treatment blocked high glucose(HG)-induced ASK1-JNK1/2 signaling activation, and excessive apoptosis in vitro. Inhibiting ASK1 via siRNA remarkably ameliorated the HG-induced increase in p-IRE1α and associated apoptosis in SH-SY5Y cells, suggesting that ASK1 is essential for the assembly and function of the proapoptotic kinase activity of the IRE1α signalosome. In summary, ER stress and ASK1-JNK1/2 signaling play causal roles in DICD development, which has crosstalk through the formation of IRE1α-TRAF2-ASK1 complex.